2020
DOI: 10.1177/0194599820961389
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Facial Nerve Outcomes After Surgical Resection of Vestibular Schwannoma

Abstract: Objective To identify clinical predictors of facial nerve (FN) outcomes after microsurgical resection of vestibular schwannoma (VS). Study Design Prospective cohort study. Setting Academic medical center. Methods Consecutive patients undergoing VS resection from November 2017 to October 2019 were included. FN function was evaluated with the House-Brackmann (HB) scale and stratified into good (HB I-II) and poor (HB III-VI) function. Analyses included descriptive statistics, correlation, and logistic regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 80 publications
2
26
0
Order By: Relevance
“…The difference in statistical conclusions is caused by the inconsistency of inclusion criteria. The grade of resection is also controversial, with some studies showing no association of grade of resection with FN outcomes ( 29 ) and with other studies showing an association with poor FN outcomes ( 30 ). There was no correlation between extent of resection and prognosis of FN in our separate analysis ( Z = 1.139, p = 0.187, Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in statistical conclusions is caused by the inconsistency of inclusion criteria. The grade of resection is also controversial, with some studies showing no association of grade of resection with FN outcomes ( 29 ) and with other studies showing an association with poor FN outcomes ( 30 ). There was no correlation between extent of resection and prognosis of FN in our separate analysis ( Z = 1.139, p = 0.187, Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that each surgeon has a different strategy for tumor removal. The surgeon is commonly faced with balancing aggressive dissection to separate the nerve, which may result in injury, with less aggressive resection, which may risk tumor growth ( 30 ). For the tumor with strong adhesion, each surgeon chooses different, if the pursuit of total resection will increase the probability of FN injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although not directly evaluated in the current study as TL cases were excluded, a prior consensus statement notes the lack of high‐level evidence unequivocally supporting one approach over another 28 . Notably, despite occasional opinions to the contrary, facial nerve outcomes have been noted to be largely equitable between the RS and TL approaches in most studies and systematic reviews when accounting for tumor size 28–31 . Even the frequently referenced benefit of lower postcraniotomy headache rates after a TL approach appears limited, with multicenter cross‐sectional studies noting no statistically significant difference in the likelihood of long‐term severe headache among approaches using a disease‐specific quality of life measure 17,18 or when using the headache disability inventory 19 .…”
Section: Discussionmentioning
confidence: 89%
“…28 Notably, despite occasional opinions to the contrary, facial nerve outcomes have been noted to be largely equitable between the RS and TL approaches in most studies and systematic reviews when accounting for tumor size. [28][29][30][31] Even the frequently referenced benefit of lower postcraniotomy headache rates after a TL approach appears limited, with multicenter cross-sectional studies noting no statistically significant difference in the likelihood of long-term severe headache among approaches using a disease-specific quality of life measure 17,18 or when using the headache disability inventory. 19 Specifically, Carlson et al noted severe headaches were observed in 31% of patients undergoing a RS approach versus 32% of patients undergoing a TL approach at the time of survey.…”
Section: Discussionmentioning
confidence: 99%
“…The motivation to achieve good facial nerve function with microsurgery has been further pushed by the generally excellent outcomes reported for conventional low-dose stereotactic radiosurgery and active surveillance. Numerous past publications have identified potential contributing factors to facial nerve dysfunction in the postoperative setting, showcasing its importance within the literature (3)(4)(5)(6)(7)(8)(9). However, despite this focus on the outcome itself, few large studies have described the natural course of this dysfunction and potential predictors of recovery after it has occurred.…”
Section: Introductionmentioning
confidence: 99%